Dynamics in polyelectrolyte/microemulsion complexes. Issue 10 (28th August 2020) - Simon, Miriam; Gradzielski, Michael; Hoffmann, Ingo
Abstract : Neutron spin-echo measurements of polyacrylate/microemulsion complexes reveal a transient nature of these complexes with high exchange rates of droplets. Abstract : Oil-in-water (O/W) microemulsion droplets are convenient carriers for hydrophobic molecules in an aqueous phase and are used for a wide range of applications. We studied weakly charged O/W microemulsion droplets complexed with oppositely charged polyacrylates that form long linear arrangements of droplets. All samples showed rather low viscosities, which is in contrast to similar systems of hydrophobically interconnected droplets. Here, we applied small-angle neutron scattering, dynamic light scattering and neutron spin-echo spectroscopy to characterise the dynamic properties of polyacrylate/microemulsion complexes in order to understand the origin of the low-viscous behaviour. We found that the electrostatic interactions lead to very dynamic complexes with high exchange rates of droplets and only a fraction of the droplets is contained within the transient complexes at a given time. These results were only accessible by the combination of different methods as one method alone would have given an incomplete picture.